Leg length, sitting height and postmenopausal breast cancer risk - Mellemkjær, L (Nature Publishing Group, 2012)
BACKGROUND: Tallness has consistently been associated with an increased risk of breast cancer. We investigated the association further by decomposing height into leg length and sitting height. METHODS: From the prospective Danish cohort ‘Diet, Cancer and Health’, 23 864 postmenopausal women enrolled during 1993–1997 were followed for a diagnosis of breast cancer in the Danish Cancer Registry through 2009. RESULTS: The incidence rate ratios for breast cancer were 1.11 (95% CI=1.06–1.16) for each 5 cm increase in total height and 1.09 (95% CI=1.01–1.17) and 1.14 (95% CI=1.04–1.25) for each 5 cm increase in leg length and sitting height, respectively. There was no statistical significant difference between the associations for leg length and sitting height (P=0.47). CONCLUSION: Leg length does not seem to be more strongly associated with breast cancer among postmenopausal women than sitting height.